Allelopathy and resource competition: the effects of Phragmites australis invasion in plant communities - Md Nazim Uddin (Botanical Studies, 2017)
Abstract Background Phragmites australis, a ubiquitous wetland plant, has been considered one of the most invasive species in the world. Allelopathy appears to be one of the invasion mechanisms, however, the effects could be masked by resource competition among target plants. The difficulty of distinguishing allelopathy from resource competition among plants has hindered investigations of the role of phytotoxic allelochemicals in plant communities. This has been addressed via experiments conducted in both the greenhouse and laboratory by growing associated plants, Melaleuca ericifolia, Rumex conglomeratus, and model plant, Lactuca sativa at varying densities with the allelopathic plant, P. australis, its litter and leachate of P. australis litter. This study investigated the potential interacting influences of allelopathy and resource competition on plant growth–density relationships. Results In greenhouse, the root exudates mediated effects showed the strongest growth inhibition of M. ericifolia at high density whereas litter mediated results revealed increased growth at medium density treatments compared to low and high density. Again, laboratory experiments related to seed germination and seedling growth of L. sativa and R. conglomeratus exhibited phytotoxicity decreased showing positive growth as plant density increased and vice versa. Overall, the differential effects were observed among experiments but maximum individual plant biomass and some other positive effects on plant traits such as root and shoot length, chlorophyll content occurred at an intermediate density. This was attributed to the sharing of the available phytotoxin among plants at high densities which is compatible to density-dependent phytotoxicity model. Conclusions The results demonstrated that plant–plant interference is the combined effect of allelopathy and resource competition with many other factors but this experimental design, target-neighbor mixed-culture in combination of plant grown at varying densities with varying level of phytotoxins, mono-culture, can successfully separate allelopathic effects from competition.